Islamic Education Based Culture: An Effort on Arranging a Humanist Society - Muhammad Yusuf; Suci Dwi Astuti; Siti Roudhotul Jannah; Siti Rusmiyatun (Institut Agama Islam Ma`arif NU (IAIMNU) Metro Lampung, 2021)
Islamic education in a multiethnic and cultural society requires special attention. Inorder to create humanist society, the implementation of Islamic education carried out in a balanced way that does not hurt certain ethnic groups. Therefore, the approach to Islamic education using cultural elements is the right strategy. The research method is descriptive qualitative which aims to describe the application of culture-based Islamic education. The findings of this study indicate that the Bumi Agung village community, Pesawaran Regency is a heterogeneous community, both ethnicity, culture and religion. Therefore, the application of Islamic education in the village of Bumi Agung appears on events such as weddings, births and deaths. therefore, Islamic education in this community has been integrated with the local community.